The Era of Internet of Things Towards a Smart World - Mohamed, Khaled Salah (Springer International Publishing : Imprint: Springer, 2019)
This book introduces readers to all the necessary components and knowledge to start being a vital part of the IoT revolution. The author discusses how to create smart-IoT solutions to help solve a variety of real problems. Coverage includes the most important aspects of IoT architecture, the various applications of IoT, and the enabling technologies for IoT. This book presents key IoT concepts and abstractions, while showcasing real case studies. The discussion also includes an analysis of IoT strengths, weaknesses, opportunities and threats. Readers will benefit from the in-depth introduction to internet of things concepts, along with discussion of IoT algorithms and architectures tradeoffs. Case studies include smart homes, smart agriculture, and smart automotive. Provides readers with a comprehensive overview of IoT; Includes discussion of IoT algorithms and architectures tradeoffs; Uses real, industrial applications/case-studies to demonstrate concepts introduced.